Resilience of Families of Different Religions in Indonesia between Social and Religious Problems - Danu Aris Setiyanto (AL-HUKAMA: The Indonesian Journal of Islamic Family Law, 2022)
Abstract : Families of different religions are a social fact in plural social life. However, interfaith marriage has always been a controversy and is considered to cause several problems, especially legal, social, and religious debates. Interestingly, some families of different religions can have good family resilience in their conditions facing social problems and religious debates. This article will answer academic anxiety about strengthening family resilience after marriage. We answer this problem with case studies and use a sociological approach.  The purpose of this article is used to explain that interfaith families have specific strategies for maintaining the resilience of their families. So, the contribution of theories and experiences of families of different religions needs to be studied in more detail through this article and subsequent research. This article produces an answer that strengthening the resilience of families of couples of different religions is carried out by mutual agreement on childcare, sharing experiences for prospective families of different religions, consultations, and couple communication that does not lead to theological differences. Abstrak : Keluarga yang berbeda agama adalah fakta sosial dalam kehidupan sosial yang majemuk. Namun, pernikahan beda agam selalu menjadi kontroversi   dan dianggap menimbulkan sejumlah masalah, terutama perdebatan hukum, sosial, dan agama. Menariknya, beberapa keluarga yang berbeda agama mampu memiliki ketahanan keluarga yang baik dalam kondisi menghadapi masalah sosial dan perdebatan agama. Artikel ini akan menjawab kecemasan akademis tentang penguatan ketahanan keluarga setelah menikah. Kami menjawab masalah ini dengan studi kasus dan menggunakan pendekatan sosiologis.   Tujuan artikel ini digunakan untuk menjelaskan bahwa keluarga beda agama memiliki strategi khusus untuk menjaga ketahanan keluarga mereka. Jadi kontribusi teori dan pengalaman keluarga dari agama yang berbeda perlu dipelajari secara lebih rinci melalui artikel ini dan penelitian selanjutnya. Artikel ini menghasilkan jawaban bahwa penguatan ketahanan keluarga pasangan yang berbeda agama dilakukan dengan kesepakatan bersama tentang pengasuhan anak, berbagi pengalaman bagi calon keluarga yang berbeda agama, konsultasi, dan komunikasi pasangan yang tidak mengarah pada perbedaan teologis.